Historical and contemporary perspectives of the Nyonya food culture in Malaysia - Ng, Chien Y.; Abdul Karim, Muhammad Shahrim (Elsevier, 2016)
Nyonya cuisine echoes the cultural identity of the Peranakans, who are both Chinese and localized. Despite the fact that the food is much localized, its symbolism remains traditionally Chinese. This paper explores the history, ingredients, and cooking methods crucial in the production of the cuisine, the types of food served for daily consumption, festivities and ancestral worships, as well as their Chinese symbolism. Furthermore, this paper also discusses factors that contributed to the obscurity of the culture and the cuisine after the Second World War. Lastly, the revival of the culture through the immense interest in its cuisine, especially from the 1980s, and the extent of globalization of this cuisine are also examined. Findings reported are expected to highlight the significance of Nyonya cuisine in Malaysia in the past and the present.